Staging Anxiety in Rachel Aberle’s Still/Falling - Tomkinson, Matthew (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (University of Toronto Press, 2020)
Still/Falling (2016) is a play for young audiences, written by Rachel Aberle, and produced by Green Thumb Theatre in Vancouver. This forum article critically examines the play’s role in local high-school curriculum through the lens of three topics: pedagogy, staging, and terminology. In particular, the article argues that a number of elements—including questions posed to students in the play’s study guide, symbols chosen to represent mental illness in the play, and mental health discourse surrounding the production—work against Green Thumb’s mandate to challenge stigma around mental illness. To combat stereotypes, a greater sense of ambiguity and complexity in these three areas is called for.